The supramolecular host-guest complexation of Vemurafenib with β-cyclodextrin and cucurbit[7]uril as drug photoprotecting systems: A DFT/TD-DFT study - Abdulilah Dawoud Bani-Yaseen (14152812) (2020)
The supramolecular host-guest complexation of the first-line anticancer drug Vemurafenib (VFB) with β-cyclodextrin (β-CD) and cucurbit[7]uril (CB7) is computationally investigated employing the DFT/TD-DFT method in implicit aqueous solutions. The structures of the 1:1 complexes of VFB:β-CD and VFB:CB7 are stabilized by intermolecular hydrogen bonds (HB) that are oriented at the rims of the host molecules with an average length of 2.00 Å. The results of the thermodynamic quantities revealed Δ G° values of −15.3 and −6.2 kcal/mol associated with the formation of VFB:β-CD-I and VFB:CB7-I complexes, respectively. These results suggest that the supramolecular host-guest complexation of VFB with β-CD is favored over CB7, which in turn can be attributed to the formation of cooperative HBs. The stability of the examined complexes was verified as revealed by molecular dynamics analyses, where these complexes exhibited changes of only ±0.02 kcal/mol and ±0.06 Å in their total energy and length of key HBs, respectively. Other Information Published in: Computational and Theoretical Chemistry License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.comptc.2020.113026